Practical Earthquake Protection of Multi-Story Buildings Using Shape Memory Alloy (SMA) Braces - Narjabadifam, Peyman; Hejazirad, Farnaz (International Journal of Scientific Research in Civil Engineering, 2018)
Shape memory alloys (SMAs) are unique materials well suited to be used in structural earthquake engineering applications. The uniqueness arises from two specific behaviors known as shape memory effect and superelasticity, and the suitability is mainly because of the superelastic behavior. Superelastic SMAs can be used as braces to protect structures against earthquakes, both for earthquake-resistant design and anti-seismic retrofit purposes. This paper reports on an applied research in this field, including also a case study. The case study building is a typical 4-story residential building with steel braced frames, located in Khorramshahr, Iran. Direct displacement-based design method is followed for the calculation of the dimensions of SMA elements. The superelastic behavior of SMAs is simulated through the phenomenological modeling, verified by experimental evaluations. Seismic performances are studied in details and it is shown that such an application is feasible and effective. Earthquake-resistant design and anti-seismic retrofit using SMA braces considerably reduce the base Shears, story accelerations, and inter-story drifts compared to the traditional earthquake-resistant design and retrofit with steel braces. It is also indicated that the residual displacements are comparably smaller in the cases of using SMA braces.
Keywords: Shape Memory Alloy; Earthquake Protection; Earthquake-Resistant Design; Anti-Seismic Retrofit